A prospective and comparative study between pre and post intra-articular knee injection to evaluate the efficacy of sodium hyaluronate (Hyruan®III) in the treatment of knee osteoarthritis - Jaruwangsanti, MD, Nara; Tienboon, MD, Prakit (Journal of Southeast Asian Orthopaedics, 2022)
Background: Many reports of sodium hyaluronate intra-articular injections into the knee joint show evidence of improvements of pain and function in osteoarthritis knees. Most of the injection techniques were a single dose once a week for 3 or 5 weeks according to each manufactures’ recomendation. Some manufactures prepared this for one single dose, one injection. Objective: To elucidate a technique of three-in-one single doses of the intra-articular injection of sodium hyaluronate for osteoarthritis of the knee with regards to its safety and clinical outcomes between pre and post injection. Methods: We combined three intra-articular injections of the high molecular weight sodium hyaluronate into a single dose to be administered as one single intra-articular injection to treat 100 osteoarthritis knees who failed the medical conservative treatment and physical therapy. The Visual Analogue Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score, Knee Society score, and knee function score were the measurement methods. The mean difference between pre and post intra-articular injections in each efficacy score was compared and the safety of the injection was the main principle of evaluation. Results: Ten knees were excluded due to not fulfilling the criteria. Only 90 knees were included. Using the Ahlback knee grading system, 60 knees were of grade I, 15 knees were of grade II, and 15 knees were of grade III. The average 100 mm VAS scale before injection was 44.26 and was reduced to its lowest point 7.41 at the 8th month follow up(P = 0.008), and increased to 36.85 at the 8th month after treatment. WOMAC scores were reduced to their lowest point 7.51at 8th month follow up (P = 0.011), and increased after 8 months after treatment to 36.75, therefore the VAS scale and WOMAC score decreased significantly. The average Knee Society score was 64.23 before injection and was raised to an average of 78.82 by the first month after injection (P = 0.002). At the 8th month after injection, the value was raised up to 90.20 (P=0.001). The average knee function score was 60.61 before injection. But after the first month post-injection, the average score was raised to 77.22, (P = 0.018). At the 8th month after injection, the value was 86.28(P = 0.001), therefore the knee score and functional score increased significantly. Conclusion: The combined three to one single dose (high molecular weight) sodium hyaluronate (Hyruan®III) injection yielded high potency of clinical results comparing between pre and post injection in all indicators in this study.